Kinerja Infrastruktur Pelayanan Jaringan Jalan Kabupaten di Wilayah Pengembangan Timur Kabupaten Bogor - Djakapermanan, Ruchyat Deni; Hidayat, Janthy Trilusianthy (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The Eastern Development Region (WP Timur) of Bogor Regency, consisting of 7 districts, holds a strategic position and is experiencing rapid development. WP Timur is currently in the process of forming a new